Post-polypectomy electrocoagulation syndrome: a rare cause of acute abdominal pain - Asad Jehangir; Kyle M. Bennett; Andrew C. Rettew; Opeyemi Fadahunsi; Bilal Shaikh; Anthony Donato (Greater Baltimore Medical Center, 2015)
While generally safe, the most feared complication of colonoscopy is perforation of the colon, occurring in nearly 1 in 1,000 procedures, and is more common when polypectomy is performed and electrocautery is used. Less commonly known is the post-polypectomy electrocoagulation syndrome, a transmural burn of the colon which mimics the signs and symptoms of perforation as well as the time course, but follows a benign course and can be treated conservatively.